US consumer interest in non-cigarette tobacco products spikes around the 2009 federal tobacco tax increase. Issue 4 (5th February 2014) - Jo, Catherine L; Ayers, John W; Althouse, Benjamin M; Emery, Sherry; Huang, Jidong; Ribisl, Kurt M
Abstract : Objectives: This quasi-experimental longitudinal study monitored aggregate Google search queries as a proxy for consumer interest in non-cigarette tobacco products (NTP) around the time of the 2009 US federal tobacco tax increase. Methods: Query trends for searches mentioning common NTP were downloaded from Google's public archives. The mean relative increase was estimated by comparing the observed with expected query volume for the 16 weeks around the tax. Results: After the tax was announced, queries spiked for chewing tobacco, cigarillos, electronic cigarettes ('e-cigarettes'), roll-your-own (RYO) tobacco, snuff, and snus. E-cigarette queries were 75% (95% CI 70% to 80%) higher than expected 8 weeks before and after the tax, followed by RYO 59% (95% CI 53% to 65%), snus 34% (95% CI 31% to 37%), chewing tobacco 17% (95% CI 15% to 20%), cigarillos 14% (95% CI 11% to 17%), and snuff 13% (95% CI 10% to 14%). Unique queries increasing the most were 'ryo cigarettes' 427% (95% CI 308% to 534%), 'ryo tobacco' 348% (95% CI 300% to 391%), 'best electronic cigarette' 221% (95% CI 185% to 257%), and 'e-cigarette' 205% (95% CI 163% to 245%). Conclusions: The 2009 tobacco tax increase triggered large increases in consumer interest for some NTP, particularly e-cigarettes and RYO tobacco.